Learning with Coping Strategies in Solving Multi-step Arithmetic Problems Towards Numeracy Skills - Yosa, Nabhila; Amir, Mohammad Faizal; Wardana, Mahardika Darmawan Kusuma (LPPM Undiksha, 2022)
The numeracy skills of elementary school students are still inadequate in solving multi-step arithmetic problems. This study aims to analyses the effect of learning with coping strategies in improving the numeracy skills of elementary school students in solving multi-step arithmetic problems. This type of research uses a quasi-experimental design with a pretest-posttest control group. The research participants were 51 fifth grade elementary school students who were randomly assigned to the experimental and control groups. Data collection using tests with multi-step arithmetic problem instruments those are oriented towards numeracy. Data analysis in this study used a paired t-test followed by a chi-square test. The results showed that coping strategies in solving multi-step arithmetic problems had a significant effect on the achievement of increasing primary students' numeracy skills. The results of this study have implications for initial empirical evidence for educators and subsequent research those elementary school students who have inadequate numeracy skills can be improved through coping strategies which are stimulation strategies by imitating and solving multi-step arithmetic problems that have gradual completion.